Like Water-Flavored Rice - Cabugao, Nikki Manzano (Likhaan: The Journal of Contemporary Philippine Literature; Vol 17 No 1 (2023): LIKHAAN 17: The Journal of Contemporary Philippine Literature, 2023)
Through the act of preparing, cooking, and eating rice, a daughter of an overseas Filipino worker bridges the present to her childhood past in Dubai and Singapore. This essay explores the role rice plays as both personal and cultural sustenance, how it struggles to remain a constant presence in our lives, whether they are spent in the Philippines or outside the country.